Significance of establishing occlusal anatomy in operative dentistry - Sumeeta Sandhu; Jagmohan Lal; Ramanpreet Singh; Rameet Sandhu; Jobanjeet Sra (Wolters Kluwer Medknow Publications, 2016)
Healthy mouth needs a stable occlusal relationship to help in efficient mastication, maintaining vertical dimension of the face, stabilizing the arches, and protecting the soft tissues. Restorative dentistry loses its significance in the absence of good occlusion. Poorly occluding restored tooth surfaces not only provide a deleterious effect to the tooth and its associated periodontium but also to the dentition of the opposing arch. The damaging effects of premature contacts, cuspal interferences, faulty proximal contacts, etc., have an adverse influence on the overall health of stomatognathic system. In this article, the significance of establishing occlusal anatomy while restoring teeth to maintain healthy and harmonious occlusion has been described.